Ag-Catalyzed ring-opening of tertiary cycloalkanols for C–H functionalization of cyclic aldimines. Issue 12 (14th January 2021) - Wang, Jingjing; Liu, Xue; Wu, Ziyan; Li, Feng; Zhang, Ming-Liang; Mi, Yiman; Wei, Junhao; Zhou, Yao; Liu, Lantao
Abstract : Silver-catalyzed direct C–H functionalization of cyclic aldimines with cyclopropanols and cyclobutanols via a radical-mediated C–C bond cleavage strategy has been realized, generating the desired products in decent yields with wide substrate scope. Abstract : We firstly describe a silver-catalyzed direct C–H functionalization of cyclic aldimines with cyclopropanols and cyclobutanols via a radical-mediated C–C bond cleavage strategy. The desired products were generated in decent yields with wide substrate scope under mild reaction conditions. In addition, a gram-scale reaction and synthetic transformation of the product were performed.